Correlation of Total Oil Content with Planktonic Diatoms (Bacillariophyceae) in the Waters of Bengkalis Straits, Pangkalan Jambi Village Bengkalis Regency - Tane, Bintang Rapshodio; Mulyadi, Aras; Nurrachmi, Irvina (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Oil pollution in the waters is one factor affecting the abundance of phytoplankton, especially the diatoms. The waters of Bengkalis Strait, Pangkalan Jambi Village, and Bengkalis Regency are used as international shipping lanes and industrial areas. This study aims to analyze the total oil content, calculate the abundant of planktonic diatoms, and explain the relationships between the total oil content and the abundant of planktonic diatoms carried out in the Bengkalis Strait, Pangkalan Jambi Village Bengkalis Regency, Riau Province. This research uses a survey method. Station 1 is near fish ponds and mangroves, station 2 is in the harbor where the fishing boats moor, station 3 is in wharf bridge and residential areas, and station 4 is in mangrove ecotourism. The result of the oil content analysis obtained an average value of 0.216 ppm. The highest oil content at station 2 is 0.5742 ppm, and the lowest at station 4 is 0.0775 ppm. The calculations of the abundance of planktonic diatoms ranged from 3,323.28 to 11,631.48 ind/L. The highest abundance at station 3 was 9,692.2 ind/L. The lowest abundance was at Station 2, which was 4,154.1 ind/L. Simple linear regression test results obtained equation Y = 6045.927572 + (3013.071268x). The coefficient of determination (R2)= 0.049 states that 4.9% of the abundance of planktonic diatoms is influenced by oil content, and other environmental factors influence the rest. The correlation coefficient (r) = 0.0223, so the relationship between total oil content and the abundance of planktonic diatoms is very weak